Combined Schwannoma and Kappa-Restricted Plasma Cell Neoplasm: A Case Report and Review of the Literature - Jeffrey John Cannatella; Soumya Pandey (Hindawi Limited, 2021)
The patient is a 78-year-old woman with a popliteal soft tissue mass that was tender to palpation with shooting pain on physical examination. A schwannoma was seen on biopsy with subsequent excision demonstrating a concomitant kappa-restricted plasma cell neoplasm. Follow-up did not show evidence of a systemic plasma cell neoplasm. MRI studies showed no evidence of focal lesions, although PET-CT revealed presence of multiple lytic lesions. The patient is currently being monitored every six months. This case is the first kappa-restricted plasma cell neoplasm reported in association with a schwannoma and the first reported in the extremities.